The Fast Inhibitor of Tissue Plasminogen Activator in Plasma During Pregnancy - Wiman, B; Csemiczky, G; Marsk, L; Robbe, H (Thrombosis and Haemostasis, 1984)
The novel fast inhibitor to tissue plasminogen activator in plasma has been determined in 20 healthy non-pregnant women, 48 apparently healthy pregnant women and 136 women with risk pregnancies (preeclampsia, suspected fetal growth retardation, thrombosis or previous history of thrombosis, diabetes and others). In healthy fertile non-pregnant women, the inhibitor concentration was found to be 0.4 ± 0.7 U/ml. In pregnant women the concentration stayed at this level until week 10, but then an almost linear increase was found, reaching about 6.5 U/ml at week 40. In plasma samples from the patients with risk pregnancies many with deviating concentrations were found. Thus, in the last trimester a range of 0-24.0 U/ml was found in these patients, as compared to 4.0-6.4 U/ml in healthy pregnant women. The pathophysiological impact of this finding is at present unclear.
Keywords: Fibrinolysis; Plasminogen activator inhibition; Pregnancy; Risk pregnancy